8D-BIM models in construction: Enhanced occupational safety for construction works - Mariusz Szóstak; Mateusz Napiórkowski; Krzysztof Dziekoński; K.S. Anandh (Budownictwo o Zoptymalizowanym Potencjale Energetycznym)
Building Information Modelling (BIM) is a key tool supporting innovative approaches in the area of sustainable and ecological construction. Through the use of digital technologies such as BIM, it is possible to accurately plan and optimize construction processes resulting in efficient resource management, reduced energy consumption and minimized waste. BIM also allows for better collaboration between project teams, which supports the integration of sustainability efforts throughout the building lifecycle, from design, realization to operations and maintenance. In addition, the use of BIM can improve occupational health and safety (OHS) on construction sites. With detailed 3D models and simulations, potential hazards can be identified before work begins, construction site organization can be better planned and dangerous situations can be avoided. This facilitates risk management and also ensures safer working conditions for all participants in the construction process.